Respons Pertumbuhan dan Hasil Cabai (Capsicum annuum L.) terhadap Dosis NPK dan Inokulasi Fungi Mikoriza Arbuskular - Desi Ratna Sari; M.Amri; Budi Santosa (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
Arbuscular Mycorrhizal Fungi (AMF) are biological agents that play an important role in increasing the efficiency of nutrient uptake and plant tolerance to abiotic stress, especially in acidic soils such as ultisols. This study aims to analyze the growth and yield responses of chili (Capsicum annuum L.) to the combination of NPK fertilizer doses and AMF inoculation. The study was conducted in Sungai Talang, Gadut, Agam Regency, from June to October 2025 using a Factorial Completely Randomized Design with two factors, namely AMF inoculation (without AMF, Glomus sp., and Rhizophagus sp.) and NPK fertilizer doses (100%, 75%, 50%, and 25% of the recommendation). The results showed a significant interaction between AMF inoculation and NPK doses on plant height, dry weight, flowering time, and fruit yield per plant. Glomus sp. inoculation with a 50% NPK fertilizer dose resulted in the highest growth and yield, equivalent to the 100% NPK treatment without AMF. The integration of AMF with a 50% reduction in NPK dosage has been shown to maintain crop productivity. This strategy can serve as a basis for developing a sustainable agricultural system based on nutrient efficiency and soil microbial balance.